A 3-Year Prospective Study of Parent–Child Communication in Early Adolescents With Type 1 Diabetes: Relationship to Adherence and Glycemic Control - Iskander, Jeannette M. (J Pediatr Psychol, 2015)
Objective To examine changes in parent–child communication patterns and their relation to glycemic control and treatment adherence using observational data in a 3-year prospective multisite study of youth with type 1 diabetes aged 9–11 years at baseline and their families (n = 217). Methods Adolescents and caregivers participated in a diabetes problem-solving discussion. Families were rated on negative and positive communication and interactions using the Interaction Behavior Code. Results Maternal and paternal negative communication decreased over time, whereas adolescent and maternal positive communication and positive reciprocity increased. Baseline preadolescent youth and maternal positive communication predicted adherence 3 years later. Changes in family communication did not predict changes in glycemic control or adherence. Conclusions During the transition to adolescence, family communication changed in unexpected and positive ways. Additionally, the relationship of baseline family communication to subsequent adherence suggests the need to assess family communication concerning diabetes-related management during preadolescence.